Move your mind: embedding accredited exercise physiology services within a hospital-based mental health service. (February 2021) - Furzer, Bonnie J; Wright, Kemi E; Edoo, Azam; Maiorana, Andrew
Objective: Despite support for the role of exercise in improving physical and mental health for various psychiatric disorders, few service implementation evaluations within diverse hospital environments exist. This study presents the feasibility and implementation of a clinical exercise physiology service within a hospital mental health service. Method: Feasibility and service data were collected from databases and self-report (consumer and staff) for 6 months from the commencement of new exercise services (gym and group sessions) for community and inpatients (one secure and three open wards). Results: One hundred and twenty consumers engaged with exercise services with 70 direct referrals over the 6-month audit period (mean age 40 ± 13 years (19–69); 41% male). The overwhelming reason for referral was related to weight loss/management (65.7%), with the majority of patients (51%) presenting with schizophrenia spectrum and other psychotic disorders. Further, 549 exercise service interactions were delivered and 78% gym attendees and 69% group session attendees rated the exercise sessions as 'Good' or 'Great', and intention to return ranged from 78% for inpatient gym sessions to 91% for community gym sessions. Conclusions: Embedding exercise physiology into a mental health service is feasible and well accepted and the evaluation of long-term consumer outcomes in 'real-world' will serve as a crucial step.